2019
DOI: 10.1111/ijsa.12238
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning from recruit to officer: An investigation of how stress appraisal and coping influence work engagement

Abstract: This study investigated stress, coping, and work engagement among Portuguese police officers while undergoing academy training and then 1 year later, when on duty. It was hypothesized that stress appraisal and coping preferences predicted engagement. Additionally, in order to test a full cross‐lagged prediction model, it was hypothesized that stress, coping, and engagement in recruits predicted these variables later when working as police officers. Structural equation modeling was used to test the research hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 54 publications
0
4
0
1
Order By: Relevance
“…Combinations of measures may improve the study of stress among police by allowing researchers to investigate the ways in which the cognitive process of appraisal acts as a mediator when confronted with a stressor (Robinson 2018). This approach may enhance the current situation, as some researchers have argued that studies of stress among police mainly focus on the nature of stressors without interpreting their results through a theoretical framework of stress (Rodrigues et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combinations of measures may improve the study of stress among police by allowing researchers to investigate the ways in which the cognitive process of appraisal acts as a mediator when confronted with a stressor (Robinson 2018). This approach may enhance the current situation, as some researchers have argued that studies of stress among police mainly focus on the nature of stressors without interpreting their results through a theoretical framework of stress (Rodrigues et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary appraisals concern coping options based on available social and organisational resources and the amount of control that individuals feel they have over the situation. The appraisal processes and subsequent reappraisals are governed by the cumulative sum of contextual, situational, or private disturbances (Evans and Coman 1993;Gächter et al 2011) and are a function of demands, available internal or external resources, and support (Rodrigues et al 2019). Thus, the same situation or difficulty may be interpreted as harmless by one individual and as stressful by another (McEwen and Sapolsky 1995;Yaribeygi et al 2017).…”
Section: Stress As a Phenomenonmentioning
confidence: 99%
“…foi alto e significativamente diferente dos níveis médios daqueles com tempo de serviço a partir de 21 anos. Um estudo semelhante sobre a relação entre Burnout e tempo de serviço (24) mostrou um ligeiro declínio proporcional ao tempo de serviço após um pico inicial. Dentro das estratégias de sobrevivência (22) , verifica-se que, para Embora estudos (16,27) estresse negativo (28) .…”
Section: Resultsunclassified
“…For example, Rothmann, Jorgensen and Marais [49] reported that high problem-focused, seeking social support, turning to religion and low ventilation of emotions predicted work engagement. Thus, Rodrigues et al [57] found that coping and stress appraisals do not seem to predict work engagement. Although some authors argue that COP and SOC constructs are likely to reduce individual level of stress [44].…”
Section: Cop As Moderatormentioning
confidence: 99%